Deep co-added sky from Catalina Sky Survey images. Issue 4 (10th August 2021) - Singhal, Akshat; Bhalerao, Varun; Mahabal, Ashish A; Vaghmare, Kaustubh; Jagade, Santosh; Kulkarni, Sumeet; Vibhute, Ajay; Kembhavi, Ajit K; Drake, Andrew J; Djorgovski, S George; Graham, Matthew J; Donalek, Ciro; et al.
ABSTRACT: A number of synoptic sky surveys are underway or being planned. Typically, they are done with small telescopes and relatively short exposure times. A search for transient or variable sources involves comparison with deeper baseline images, ideally obtained through the same telescope and camera. With that in mind, we have stacked images from the 0.68 m Schmidt telescope on Mt. Bigelow taken over 10 yr as part of the Catalina Sky Survey. In order to generate deep reference images for the Catalina Real-time Transient Survey (CRTS), close to 0.8 million images over 8000 fields and covering over 27 000 sq. deg have gone into the deep stack that goes up to 3 mag deeper than individual images. CRTS system does not use a filter in imaging; hence, there is no standard passband in which the optical magnitude is measured. We estimate depth by comparing these wide-band unfiltered co-added images with images in the g band and find that the image depth ranges from 22.0 to 24.2 across the sky, with a 200-image stack attaining an equivalent AB magnitude sensitivity of 22.8. We compared various state-of-the-art software packages for co-adding astronomical images and have used swarp for the stacking. We describe here the details of the process adopted. This methodology may be useful in other panoramic imaging applications, and to other surveys as well. The stacked images are available through a server at Inter-University Centre for Astronomy and Astrophysics.